Sport club dropout under COVID-19 in the Netherlands: do characteristics of the neighbourhood matter? - Hoekman, Remco; Grubben, Malou; Kraaykamp, Gerbert (Frontiers in Sports and Active Living, 2023)
Sport is considered important to mitigate social and health problems related to the COVID-19 pandemic and thus contributes to a resilient society. Because of poverty, caring responsibilities, social isolation and/or health issues, caused or reinforced by the COVID-19 pandemic, (too) high thresholds may be experienced lowering sports club participation. In this article, we study dropout from sports club membership among the Dutch population in COVID times and relate it to neighbourhood characteristics to determine whether inequality in sports behaviour is increasing or decreasing. Specifically, we analyse changes in the association to sport clubs by utilizing membership register data of the National Sport Federation in the Netherlands (NOC*NSF). This longitudinal information on 3.6 million club members in 2019 within Dutch sport federations was used to analyse developments at the individual level between 2019 (pre-COVID) and 2021. Based on register information on the area of residence of sporters, neighbourhood characteristics were added to these individual membership data. Our results display that the socioeconomic status of a member's neighbourhood and the sport infrastructure in this neighbourhood impacts the likelihood of dropping out of a sport club of both youths and adults during the COVID-19 pandemic. Dropout among members is lower in higher socioeconomic status neighbourhoods and in neighbourhoods with abundant sport facilities. Remarkably, the impact of these living environment features seems higher for youth than for adults. To conclude, our study enhances a further understanding of inequalities in sport club membership dropout during COVID-19. First, it may inform policy makers to intensify sport promotion policies and to especially support sport clubs in lower status neighbourhoods. Second, given the relatively high dropout rates during the COVID-19 pandemic particular attention for retention seems necessary.